CYSTS OF SMALL SALIVARY GLANDS: CLINICAL AND MORPHOLOGICAL ASPECTS - Tkachenko, P.I.; Starchenko, I.I.; Belokon, S.A.; Gogol, A.M. (World of Medicine and Biology, 2012)
The article presents the pathogenetic links of small cysts of salivary glands. Cystectomy is 6,2% of the total number of planned outpatient surgical procedures in children. Special attention is paid to the variations of the morphological structure of these cysts, which depending on the characteristics of their clinical course.